Review on dye-sensitized solar cells based on polymer electrolytes - Soonmin, Ho; Shanmugam, Mariyappan; Mordiya, Meet; Markna, Jaysukh H. (International Journal of Engineering and Technology, 2018)
Dye-sensitized solar cells (DSSCs) have received significant attention due to easy fabrication process, environmental friendli-ness, low production cost, simple structure and high power conversion efficiency. This type of solar cell can convert visible light into electricity. Light is absorbed by a sensitizer, in order to harvest a large fraction of sunlight. Researchers reported DSSCs using polymer electrolyte exhibiting better stability than the DSSCs with liquid electrolyte. Overall solar (standard AM 1.5) to current conversion efficiencies over 9 % have been reached.